Internationalizing China : domestic interests and global linkages - Zweig, David (Ithaca : Cornell University Press, 2002)
China began opening to the outside world in 1978. This process was designed to remain under the state's control. But the relative value of goods and services inside and outside China drove cities, enterprises, local governments, andindividuals with comparative advantage in international transactions to seek global linkages. These contacts, David Zweig asserts, led to the deregulation of China's mercantilist regime. Through extensive field research, Zweig surveys the extraordinary changes in four sectors of China's domestic political economy: the establishment of developmentzones, rural joint ventures, the struggle over foreign aid and higher education. He also addresses the crucial question of whether, on balance, internationalization weakens or strengthens state power.
Explaining internationalization : channels, resources, and fevers -- Segmented deregulation and the politics of urban internationalization -- Internationalizing rural China : exports, foreign direct investment, and developmental communities -- Dollars, scholars, and fevers : the political economy of educational internationalization -- Controlling the opening : the struggle over overseas development assistance.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: China -- Foreign economic relations; China -- Commercial policy; China -- Economic policy -- 2000-; Investments, Foreign -- China; Globalization -- Economic aspects -- China; Investissements étrangers -- Chine; Mondialisation -- Chine; Chine -- Relations économiques extérieures.; Chine -- Politique commerciale; Chine -- Politique économique -- 2000-; BUSINESS & ECONOMICS -- International -- Economics; BUSINESS & ECONOMICS -- International -- General; POLITICAL SCIENCE -- Political Economy; Commercial policy; Economic policy; Globalization -- Economic aspects; International economic relations; Investments, Foreign; China; Auslandsinvestition; Außenwirtschaftspolitik; Internationalisierung; China; Internationalisatie; Buitenlandse betrekkingen; Binnenlandse politiek; Mondialisation -- Aspect économique -- Chine; Investissements étrangers -- Chine; Politique commerciale -- Chine -- 1970-2000.; Chine -- Politique commerciale; Chine -- Politique économique.; Chine -- Relations économiques extérieures.; Relations économiques extérieures.; Politique économique.; Politique commerciale; Investissement étranger.; Mondialisation; Chine; Since 2000